Broadband Access Communication Technologies XIV 2020
DOI: 10.1117/12.2548146
|View full text |Cite
|
Sign up to set email alerts
|

An end-to-end 5G automotive ecosystem for autonomous driving vehicles

Abstract: DOI to the publisher's website.• The final author version and the galley proof are versions of the publication after peer review.• The final published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The proposed MISO processing results in improved receiver sensitivity due to the enhancement in SNR and thus improves the power efficiency of the overall system as the photodetector requires a reduced amount of power to provide the same BER performance, as in the case of MISO with a conventional receiver. Even in the presence of strong interference signal, the proposed framework shows successful transmission of much higher data rates as compared to [27], and three times longer transmission distance as compared to the previously reported MIMO-based VLC transmission [30]. This shows the superiority of the proposed MISO receiver in the VLC-based ITS, which is evident from the provision of higher data rates, longer transmission distances and improved receiver sensitivity than recently proposed solutions [31].…”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…The proposed MISO processing results in improved receiver sensitivity due to the enhancement in SNR and thus improves the power efficiency of the overall system as the photodetector requires a reduced amount of power to provide the same BER performance, as in the case of MISO with a conventional receiver. Even in the presence of strong interference signal, the proposed framework shows successful transmission of much higher data rates as compared to [27], and three times longer transmission distance as compared to the previously reported MIMO-based VLC transmission [30]. This shows the superiority of the proposed MISO receiver in the VLC-based ITS, which is evident from the provision of higher data rates, longer transmission distances and improved receiver sensitivity than recently proposed solutions [31].…”
Section: Resultsmentioning
confidence: 62%
“…Recent field trials on VLC-based ITS have demonstrated a lot of advantages of using illumination purposed LEDs for road safety and traffic control [28][29][30]. Aside from the proven advantages (such as high levels of integration with existing infrastructure, transmission up to 50 m distance, etc.)…”
Section: Related Work and Contributionmentioning
confidence: 99%
“…An example of connected vehicles, base stations, roadside units, edge-servers, infrastructure and remote cloud is shown in Figure 3. Several use-cases presented within the context of vehicle communication [218], [252], [22], [96], [212], [52], discuss directly benefiting the perception, planning, and control related use-cases using distributed or jointinference. However, little attention has been given to energy efficiency.…”
Section: E Communications In Autonomous Vehiclesmentioning
confidence: 99%
“…NR V2X: New Radio (NR) V2X is designed to complement the applications that are not fully supported in C-V2X because of varied latency, bandwidth and throughput requirements [218]. NR V2X use-cases comprises of efficient and reliable delivery of aperiodic messages, which was not very well supported in C-V2X [252], [22]. As compared to V2X, NR V2X also supports groupcast and broadcast transmission methods which are specifically required for applications such as vehicle platooning [218], [22], [52].…”
Section: Vehicular Communicationmentioning
confidence: 99%